Marked Antigiardial Activity of Yucca baccata Extracts: A Potential Natural Alternative for Treating Protozoan Infections. (31st August 2014) - Quihui-Cota, Luis; León-Trujillo, Rocio; Astiazarán-García, Humberto; Esparza-Romero, Julián; Robles, María del Refugio; Robles-Zepeda, Ramón E.; Canett, Rafael; Sánchez-Escalante, Jesús
Abstract : Human Giardiosis is a public health problem in Mexico, where the national prevalence was estimated to be up to 68%. Misuse of antiprotozoal drugs may result in low effectiveness and undesirable side effects. Research on natural products is a good strategy for discovering more effective antiparasitic compounds. This study evaluated the antigiardial activity of extracts of Yucca baccata, which is native to northwestern Mexico. Forty-two gerbils (females) were weighed and orally inoculated with 5 × 10 6 Giardia trophozoites. Two gerbils were selected at random to confirm infection. Forty living gerbils were randomly allocated into 5 treatment groups (8 per group). Gerbils were randomly assigned to be treated with 24.4 mg/mL, 12.2 mg/mL, and 6.1 mg/mL of extracts, metronidazole (2 mg/mL) or PBS, which were intragastrically administered once per day for 3 days. Nine gerbils died during the study course. On day 10 postinfection, gerbils were euthanized and trophozoites were quantified. Yucca extracts reduced, albeit not significantly, the trophozoite counts in the duodenum segment. Only the high-extract concentration significantly reduced the trophozoite counts in the proximal segment and it was similar to that of metronidazole. Extracts of Y. baccata may represent an effective and natural therapeutic alternative for human giardiosis.